The Effect of Work Motivation on Employee Performance with Work Discipline as an Intervening Variable at BSI KCP Kuala Meulaboh - ZD, Murtaza; Yulia, Cut Dwi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The performance of BSI KCP Kuala Meulaboh employees was previously good and even reached the target desired by the bank, but now employee performance has decreased, this happens because employees are slow in doing their jobs, making it very difficult to achieve targets. The motivation given by the leadership is very good but the performance is inversely proportional. There are still employees who are less motivated, this is caused by the personality of each employee. There are employees who feel they cannot work together with their team so that their motivation to work is lacking. The purpose of this study was to determine whether or not there is an effect of work motivation on employee performance with work discipline as an intervening variable on BSI KCP Kuala Meulaboh employees. The location of this research was BSI KCP Kuala Meulaboh which is located on Jalan Meulaboh - Jeuram Gampong Simpang Peut, Nagan Raya Regency. The sample in this study was 17 BSI KCP Kuala Meulaboh employees. The objects in this study were motivation, employee performance and work discipline. Based on the results of the study, it shows that there is an influence of work motivation (X) on the performance (Y) of BSI KCP Kuala Meulaboh employees, with a significant value obtained of 0.016 (0.016 <0.05), which means it has an effect. There is an influence of work motivation (X) on work discipline (Z) of BSI KCP Kuala Meulaboh employees, with a significant value obtained of 0.004 (0.004 <0.05), which means it has an effect. There is an influence of work discipline (Z) on the performance (Y) of BSI KCP Kuala Meulaboh employees, with a significant value obtained of 0.001 (0.001 <0.05), which means it has an effect. There is an influence of work motivation on employee performance with work discipline as an intervening variable for BSI KCP Kuala Meulaboh employees, amounting to 73.8%.